2012
DOI: 10.1590/s1413-70542012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of the rainfall erosivity in southern region of Minas Gerais state, Brazil

Abstract: Rainfall erosivity and its spatial variability were studied for 54 pluviometric stations in Southern Minas Gerais State (48º00' -44º00'W; 23º50' -20º00'S), aiming to plan the land-use strategies. Therefore, erosivity factor was determined for the pluviometric stations, using long-term rainfall data sets obtained along with the Brazilian National Water Agency-ANA, which varied from 15 to 40 years. The monthly and annual erosivity indexes were generated using Fournier equation for Lavras, MG and the spatial dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
3
18
0
13
Order By: Relevance
“…Aquino et al (2012) concluded that the erosivity of the south region of the state of Minas Gerais was considered high and strongly influenced by altitude in association with climatic characteristics. Higher erosivity is associated with higher altitude areas, such as along the Mantiqueira Range and high plateaus and mountains in the north-central part of the region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquino et al (2012) concluded that the erosivity of the south region of the state of Minas Gerais was considered high and strongly influenced by altitude in association with climatic characteristics. Higher erosivity is associated with higher altitude areas, such as along the Mantiqueira Range and high plateaus and mountains in the north-central part of the region.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of erosivity mapping on a national scale (Silva, 2004;Oliveira et al, 2012;Mello et al, 2013) and for the states of Minas Gerais (Mello et al, 2007;Moreira et al, 2008), with specific details for the south of the state of Minas Gerais (Aquino et al, 2012), and São Paulo (Vieira and Lombardi Neto, 1995;Moreira et al, 2006) showed analysis on a regional scale with low spatial resolution. However, river basins are the basic unit of planning and management of water resources, and the planning and implementation of soil and water conservation practices require a level of spatial detail consistent with their scale .…”
Section: Introductionmentioning
confidence: 99%
“…All plots were limited by a galvanized zinc metal plate, inserted 20 cm into the soil and 20 cm left over the soil surface. At each plot lower side, an outlet was set to deliver soil and water into two 250 liter reservoirs connected to each other by a GEIB divisor, with 9 entrance windows, such that after the first reservoir was completely filled, one ninth of runoff was carried to the second reservoir, such as described by Aquino et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Pode-se observar que os maiores valores de erosividade ocorrem de outubro a março e, no período de abril a setembro, são consideravelmente menores. Essa distribuição temporal é característica da região, com verão chuvoso e inverno seco, sendo que vários pesquisadores, em diversas regiões do país, têm encontrado situação semelhante (Dias & Silva, 2003;Silva et al, 2009;Bertoni & Lombardi Neto, 2010;Silva et al, 2010;Aquino et al, 2012;Aquino et al, 2013).…”
Section: Log Normal 3 Parâmetros Normalunclassified
“…Para todas as durações de chuvas intensas estudadas, as regiões norte e nordeste apresentaram as menores intensidades. Aquino et al (2012) observaram que a região sul de Minas Gerais apresenta elevada erosividade das chuvas, sendo os maiores índices observados nas áreas de maiores altitudes e nos planaltos e serras elevadas.…”
Section: Introductionunclassified